A STUDY OF THE USE OF CHILDRENâS LITERATURE IN THE TEACHING ENGLISH TO YOUNG LEARNERS AT CHILDRENâS HOUSE SCHOOL - Asmini, Ni Putu Juli (Jurnal Pendidikan Bahasa, 2012)
ABSTRACT Â  Key words: childrenâs literature, teaching English to young learners Â  This study aimed at investigating: (1) how childrenâs literature was prepared incorporated into the lesson plan; (2) how childrenâs literature was applied into the classroom; and (3) the quality of childrenâs books used as the learning media in the teaching and learning process. The subjects of this study were the young learners (children at the age of 5-6) and the teachers of Butterfly Morning class of Childrenâs House Kindergarten School. There were 15 young learners and 2 teachers involved as the research subjects. This study was a descriptive study using a mixed method of data collection and analysis. There were two types of data collected, namely: quantitative and qualitative data that embedded one within the other so that one type of the data provided a supportive role for the other datasets. The data were collected using some types of instruments, such as lesson plan checklist, observation sheet, childrenâs book checklist and interview guidance. The method of data analysis followed the concept of Miles and Huberman Model (2010) (data reduction, data display and conclusion) in which the analysis of the data used the formula of Nurkancana and Sunartana (1992). The results of the study were as follows: (1) the incorporation of childrenâs literature into the lesson plan was excellent as the lesson plan made by the teachers obtained the score of 44. The lesson plan was excellent because the format had worked in accordance with the guideline of government format in the Permen Diknas No.58/2009 and the content had followed the APKCG of Undiksha supported by the concept of literature-based instruction. (2) The implementation of childrenâs literature in the classroom was excellent as the score was 46 for Language subject, 45.3 for Language Enrichment subject and the last for Moral subject was 49. The implementation followed the lesson plan prepared and the strategy of story reading in the classroom was also excellently applied.Â Â  (3) The quality of the childrenâs books used in the classroom was excellent as it obtained the score of 15 for Language subject, 19 for Language Enrichment subject and 20 for Moral subject. The books had appropriate genres and text types, used simple and realistic dialogue and attractive illustration. Based on those findings, the study concluded that the use of childrenâs literature at Childrenâs House school, especially in Butterfly Class was excellently implemented. It could be seen from the lesson plan prepared for each lesson, the strategy chosen to be applied in the classroom and the childrenâs books used as the media of learning to help the children achieve the lesson objectives.Â ABSTRAK Kata Kunci: sastra anak-anak, pengajaran bahasa Inggris untuk anak-anak Penelitian ini bertujuan untuk mengetahui: (1) cara pengunaan sastra anak-anak dalam Rencana Pelaksanaan Pembelajaran (RPP); (2) cara pengaplikasian sastra anak-anak dalam pengajaran; dan (3) kualitas buku-buku sastra anak-anak yang digunakan. Subjek penelitian ini adalah siswa berumur 5-6 tahun yang masuk dalam kelas âButterfly Morningâ di sekolah Childrenâs House beserta guru. Terdapat 15 orang anak dan dua orang guru dalam kelas âButterfly Morningâ yang dilibatkan sebagai subjek penelitian. Penelitian ini merupakan penelitian deskriptif yang menggunakan penggabungan metode kwantitatif dan kwalitatif (mixed method). Ada dua jenis data yang dikumpulkan dalam penelitian ini, yaitu data kwantitatif dan data kwalitatif. Kedua data ini kemudian digabungkan sehingga masing-masing data dapat mendukung satu dan yang lainnya. Data dikumpulkan dengan menggunakan daftar cek untuk RPP dan buku-buku sastra anak-anak serta lembar observasi kelas dan wawancara. Metode analisis data menggunakan model Miles dan Huberman (2010) (reduksi data, penampilan data dan kesimpulan) dan analisis data yang digunakan mengikuti formula dari Nurkancana dan Sunartana (1992). Hasil penelitian menujukkan bahwa: (1) penggunaan sastra anak-anak dalam RPP sangat baik karena terlihat dari perolehan nilai pada kualitas RPP tersebut sebesar 44. Hal ini disebabkan oleh format RPP sudah mengikuti aturan yang belaku dalam Permen Diknas 58/2009 dan isi RPP yang sudah mengikuti APKCG Undiksha dan konsep pembelajaran berbasis sastra. (2) Pengaplikasian sastra anak-anak dalam pengajaran di kelas sangat baik sebab nilai dari kualitas pembelajaran tersebut adalah 46 untuk mata pelajaran âLanguageâ, 45.3 untuk mata pelajaran âLanguage Enrichmentâ dan mata pelajaran âMoralâ memperoleh nilai sebesar 49. Dalam prosesnya, pengaplikasian sastra anak-anak sudah mengikuti RPP yang telah disusun dan strategi pengajaran yang berupa pembacaan buku cerita diterapkan dengan sangat baik. (3) Kualitas buku anak-anak yang digunakan sebagai media pembelajaran sangatlah baik sebab telah memperoleh nilai 15 untuk mata pelajaran âLanguageâ, 19 untuk mata pelajaran âLanguage Enrichmentâ and 20 untuk mata pelajaran âMoralâ. Kualitas buku yang digunakan, terutama pada jenis teks sudah sesuai dengan karakteristik anak-anak, dialog yang sederhana dan realistis serta dengan ilustrasi yang menarik. Berdasarkan temuan tersebut, dapat disimpulkan bahwa penggunaan sastra anak-anak di Childrenâs House telah berhasil dengan baik. Hal ini terlihat dari RPP, strategi pembelajaran yang dipilih and juga kualitas buku cerita anak-anak yang baik.